It is currently 17 Nov 2017, 20:22

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

Author Message
TAGS:

### Hide Tags

Retired Moderator
Status: The last round
Joined: 18 Jun 2009
Posts: 1286

Kudos [?]: 1236 [0], given: 157

Concentration: Strategy, General Management
GMAT 1: 680 Q48 V34
If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

13 Jun 2010, 05:41
32
This post was
BOOKMARKED
00:00

Difficulty:

75% (hard)

Question Stats:

62% (02:22) correct 38% (02:32) wrong based on 558 sessions

### HideShow timer Statistics

If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9
[Reveal] Spoiler: OA

_________________

Last edited by Bunuel on 14 Aug 2012, 00:31, edited 1 time in total.
Edited the question.

Kudos [?]: 1236 [0], given: 157

Manager
Joined: 04 May 2010
Posts: 86

Kudos [?]: 131 [3], given: 7

WE 1: 2 yrs - Oilfield Service
Re: Interesting Absolute value Problem [#permalink]

### Show Tags

13 Jun 2010, 06:42
3
KUDOS
1
This post was
BOOKMARKED
I did it by brute force, considering all possibilities. But I'm sure someone can come up with a way to quickly identify the signs of x and y.

x + |x| + y = 7 ....1

x + |y| - y = 6 .....2

Consider x < 0
=> |x| = -x
Substitute in 1

x - x + y = 7
y = 7

Substitute in 2

x + 7 - 7 = 6
x = 6

But this violates x < 0 So our assumption was incorrect.

Consider x > 0 and y > 0
=> |x| = x and |y| = y

Substitute in 2

x + y - y = 6
x = 6

Substitute in 1

6 + 6 + y = 7
y = -5

This violates y > 0 so our assumption was incorrect.

Consider x > 0 and y < 0
=> |x| = x and |y| = -y

Substituting in 1 and 2:

2x + y = 7 .....3
x - 2y = 6 .....4

Solving we get x = 4 and y = -1
x + y = 3

Pick A.

Kudos [?]: 131 [3], given: 7

Math Expert
Joined: 02 Sep 2009
Posts: 42248

Kudos [?]: 132522 [11], given: 12324

Re: Interesting Absolute value Problem [#permalink]

### Show Tags

13 Jun 2010, 07:01
11
KUDOS
Expert's post
4
This post was
BOOKMARKED
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9

If $$x\leq{0}$$, then $$x + |x| + y = 7$$ becomes: $$x-x+y=7$$ --> $$y=7>0$$, but then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, which contradicts the initial assumption $$x\leq{0}$$. So $$x$$ can not be $$\leq{0}$$ --> hence $$x>0$$.

Similarly if $$y\geq{0}$$, then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, but then $$x + |x| + y = 7$$ becomes: $$x+x+y=12+y=7$$ --> $$y=-5<0$$, which contradicts the initial assumption $$y\geq{0}$$. So $$y$$ can not be $$\geq{0}$$ --> hence $$y<0$$.

So $$x>0$$ and $$y<0$$:
$$x+|x|+y=7$$ becomes: $$x+x+y=7$$ --> $$2x+y=7$$;
$$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Solving: $$x=4$$ and $$y=-1$$ --> $$x+y=3$$.

I feel there is an easier way, but world cup makes it harder to concentrate.
_________________

Kudos [?]: 132522 [11], given: 12324

Intern
Affiliations: NYSSA
Joined: 07 Jun 2010
Posts: 33

Kudos [?]: 12 [1], given: 2

Location: New York City
Schools: Wharton, Stanford, MIT, NYU, Columbia, LBS, Berkeley (MFE program)
WE 1: Senior Associate - Thomson Reuters
WE 2: Analyst - TIAA CREF
Re: Interesting Absolute value Problem [#permalink]

### Show Tags

18 Jun 2010, 07:23
1
KUDOS
Bunuel wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9

If $$x\leq{0}$$, then $$x + |x| + y = 7$$ becomes: $$x-x+y=7$$ --> $$y=7>0$$, but then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, which contradicts the initial assumption $$x\leq{0}$$. So $$x$$ can not be $$\leq{0}$$ --> hence $$x>0$$.

Similarly if $$y\geq{0}$$, then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, but then $$x + |x| + y = 7$$ becomes: $$x+x+y=12+y=7$$ --> $$y=-5<0$$, which contradicts the initial assumption $$y\geq{0}$$. So $$y$$ can not be $$\geq{0}$$ --> hence $$y<0$$.

So $$x>0$$ and $$y<0$$:
$$x+|x|+y=7$$ becomes: $$x-x+y=7$$ --> $$2x+y=7$$;
$$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Solving: $$x=4$$ and $$y=-1$$ --> $$x+y=3$$.

I feel there is an easier way, but world cup makes it harder to concentrate.

Why when y<0 do we get -2y?

Kudos [?]: 12 [1], given: 2

Math Expert
Joined: 02 Sep 2009
Posts: 42248

Kudos [?]: 132522 [0], given: 12324

Re: Interesting Absolute value Problem [#permalink]

### Show Tags

18 Jun 2010, 07:28
GMATBLACKBELT720 wrote:
Bunuel wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9

If $$x\leq{0}$$, then $$x + |x| + y = 7$$ becomes: $$x-x+y=7$$ --> $$y=7>0$$, but then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, which contradicts the initial assumption $$x\leq{0}$$. So $$x$$ can not be $$\leq{0}$$ --> hence $$x>0$$.

Similarly if $$y\geq{0}$$, then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, but then $$x + |x| + y = 7$$ becomes: $$x+x+y=12+y=7$$ --> $$y=-5<0$$, which contradicts the initial assumption $$y\geq{0}$$. So $$y$$ can not be $$\geq{0}$$ --> hence $$y<0$$.

So $$x>0$$ and $$y<0$$:
$$x+|x|+y=7$$ becomes: $$x-x+y=7$$ --> $$2x+y=7$$;
$$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Solving: $$x=4$$ and $$y=-1$$ --> $$x+y=3$$.

I feel there is an easier way, but world cup makes it harder to concentrate.

Why when y<0 do we get -2y?

When $$y<0$$, then $$|y|=-y$$ and $$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.
_________________

Kudos [?]: 132522 [0], given: 12324

Intern
Affiliations: NYSSA
Joined: 07 Jun 2010
Posts: 33

Kudos [?]: 12 [0], given: 2

Location: New York City
Schools: Wharton, Stanford, MIT, NYU, Columbia, LBS, Berkeley (MFE program)
WE 1: Senior Associate - Thomson Reuters
WE 2: Analyst - TIAA CREF
Re: Interesting Absolute value Problem [#permalink]

### Show Tags

18 Jun 2010, 08:17
^
Wow... confusing as heck. Essentially saying that (hypothetical number here) |-3| = -(-3), thats fine. But I kept thinking you would apply this to -y and essentially make it +y since and make them both +y...

Kudos [?]: 12 [0], given: 2

VP
Status: There is always something new !!
Affiliations: PMI,QAI Global,eXampleCG
Joined: 08 May 2009
Posts: 1283

Kudos [?]: 286 [0], given: 10

Re: Interesting Absolute value Problem [#permalink]

### Show Tags

14 Jun 2011, 03:25
for x>0 and x < 0
2x+ y = 7 and y = 7

for y>0 and y<0
x=6 and x-2y=6

for x,y<0 solution exists.
solving x=4 and y = -1

3
_________________

Visit -- http://www.sustainable-sphere.com/
Promote Green Business,Sustainable Living and Green Earth !!

Kudos [?]: 286 [0], given: 10

Intern
Joined: 09 Nov 2011
Posts: 1

Kudos [?]: [0], given: 1

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

02 Jul 2013, 06:38
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

can be done in 2.3 mins :

there are 4 cases to be tested :
1) x is -ve and y is -ve
substituting in the equation , we get x-x+y=7 and x-y-y=6 solve for x and y we get x=20 and y=7 , so x+y=27 REJECT

2)x is +ve and y is +ve

substitute in the equation, we ger x+x+y=7 and x+y-y=6 solve for x and y we get x=6 and y=-5 ,therefore x+y=1 not on list so REJECT

3) x is -ve and y is +ve

substitute , we get x-x=y=7 and x+y-y=6 solve fo x and y we get x=6 and y=7, x+y=13 not on list so REJECT

4) x is +ve and y is -ve

substitute , we get x+x=y=7 and x-y-y=6 solve for x and y , we get x=4 and y= -1 ,x+y=3 , ANSWER CHOICE

Kudos [?]: [0], given: 1

Manager
Joined: 14 Jun 2011
Posts: 84

Kudos [?]: 50 [0], given: 15

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

02 Jul 2013, 11:22
I solved in 1.36 mins
_________________

Kudos always encourages me

Kudos [?]: 50 [0], given: 15

Intern
Joined: 04 May 2013
Posts: 47

Kudos [?]: 9 [0], given: 7

Re: Interesting Absolute value Problem [#permalink]

### Show Tags

05 Jul 2013, 11:19
Bunuel wrote:
GMATBLACKBELT720 wrote:
Bunuel wrote:

If $$x\leq{0}$$, then $$x + |x| + y = 7$$ becomes: $$x-x+y=7$$ --> $$y=7>0$$, but then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, which contradicts the initial assumption $$x\leq{0}$$. So $$x$$ can not be $$\leq{0}$$ --> hence $$x>0$$.

Similarly if $$y\geq{0}$$, then $$x + |y| - y =6$$ becomes: $$x+y-y=6$$ --> $$x=6>0$$, but then $$x + |x| + y = 7$$ becomes: $$x+x+y=12+y=7$$ --> $$y=-5<0$$, which contradicts the initial assumption $$y\geq{0}$$. So $$y$$ can not be $$\geq{0}$$ --> hence $$y<0$$.

So $$x>0$$ and $$y<0$$:
$$x+|x|+y=7$$ becomes: $$x-x+y=7$$ --> $$2x+y=7$$;
$$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Solving: $$x=4$$ and $$y=-1$$ --> $$x+y=3$$.

I feel there is an easier way, but world cup makes it harder to concentrate.

Why when y<0 do we get -2y?

When $$y<0$$, then $$|y|=-y$$ and $$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Sorry, still confusing me.
I understand the first y i.e.
|y| = -y
But y < 0,
so wouldn't x + |y| - y = x - y - (-y), which would make it just x?

Kudos [?]: 9 [0], given: 7

Math Expert
Joined: 02 Sep 2009
Posts: 42248

Kudos [?]: 132522 [0], given: 12324

Re: Interesting Absolute value Problem [#permalink]

### Show Tags

05 Jul 2013, 11:30
jjack0310 wrote:
Bunuel wrote:
GMATBLACKBELT720 wrote:

Why when y<0 do we get -2y?

When $$y<0$$, then $$|y|=-y$$ and $$x+|y|-y=6$$ becomes: $$x-y-y=6$$ --> $$x-2y=6$$.

Sorry, still confusing me.
I understand the first y i.e.
|y| = -y
But y < 0,
so wouldn't x + |y| - y = x - y - (-y), which would make it just x?

When y<0, then |y|=-y: correct. But y must stay as it is.

Consider this, suppose we have only x-y=6, and I tell you that y is negative would you rewrite the equation as x-(-y)=6?

Hope it's clear.
_________________

Kudos [?]: 132522 [0], given: 12324

Senior Manager
Joined: 13 May 2013
Posts: 460

Kudos [?]: 201 [0], given: 134

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

09 Jul 2013, 16:24
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

x>0, y>0

x + (x) + y = 7
2x+y=7

x + |y| - y = 6
x + y - y = 6
x=6

2x+y=7
2(6)+y=7
y=-5

INVALID as 6>0 but -5 is not > 0

x>0, y<0

x + (x) + y = 7
2x+y=7

x + |y| - y = 6
x + (-y) - y = 6
x - 2y = 6
x = 6+2y

2(6+2y) + y = 7
12+4y+y=7
12+5y=7
5y+-5
y=-1

2x+y=7
2x + (-1) = 7
2x - 1 = 7
2x=8
x=4

VALID as 4>0 and -1<0

therefore;

x+y = (4)+(-1) = 3

(A)

Kudos [?]: 201 [0], given: 134

Non-Human User
Joined: 09 Sep 2013
Posts: 15708

Kudos [?]: 281 [0], given: 0

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

03 Sep 2014, 11:18
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 281 [0], given: 0

Non-Human User
Joined: 09 Sep 2013
Posts: 15708

Kudos [?]: 281 [0], given: 0

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

27 Sep 2015, 15:44
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 281 [0], given: 0

Veritas Prep GMAT Instructor
Joined: 16 Oct 2010
Posts: 7736

Kudos [?]: 17766 [1], given: 235

Location: Pune, India
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

28 Sep 2015, 00:10
1
KUDOS
Expert's post
1
This post was
BOOKMARKED
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9

In such a question, you can use some brute force and get to the answer too. How long it takes depends on how quickly you observe the little things.

x + |x| + y = 7
x + |y| - y =6

Both equations yield about the same result though in one y is positive and in the other it is negative. |x| and |y| are positive and assuming x is positive, a negative y would pull down the first equation and pump up the second one to give almost equal values. The difference is very small also signifies that the negative variable might have a very small value.
Since the options give the value of x + y as 3/4/5... etc, it is likely that we are dealing with small number pairs such as (4, 2), (3, 2), (4, 1) etc.
Since the first equation has 7 as the result, both variables will not be even.
A couple of quick iterations brought me to (4, -1).
So x + y = 3
_________________

Karishma
Veritas Prep | GMAT Instructor
My Blog

Get started with Veritas Prep GMAT On Demand for \$199

Veritas Prep Reviews

Kudos [?]: 17766 [1], given: 235

Manager
Joined: 08 Sep 2012
Posts: 66

Kudos [?]: 15 [0], given: 251

Location: India
Concentration: Social Entrepreneurship, General Management
WE: Engineering (Investment Banking)
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

24 Oct 2015, 07:05
VeritasPrepKarishma wrote:
Hussain15 wrote:
If x + |x| + y = 7 and x + |y| - y =6 , then x + y =

A. 3
B. 4
C. 5
D. 6
E. 9

In such a question, you can use some brute force and get to the answer too. How long it takes depends on how quickly you observe the little things.

x + |x| + y = 7
x + |y| - y =6

Both equations yield about the same result though in one y is positive and in the other it is negative. |x| and |y| are positive and assuming x is positive, a negative y would pull down the first equation and pump up the second one to give almost equal values. The difference is very small also signifies that the negative variable might have a very small value.
Since the options give the value of x + y as 3/4/5... etc, it is likely that we are dealing with small number pairs such as (4, 2), (3, 2), (4, 1) etc.
Since the first equation has 7 as the result, both variables will not be even.
A couple of quick iterations brought me to (4, -1).
So x + y = 3

Hi Karishma,

I tried another approach, but got stuck - can you hep me solve by this method?
x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E
x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y
Now x + y = 7 - |6 + 2y|
If we take y = -1, we get x + y = 3 = Option A
If we take y = -2, we get x + y = 5 = Option C
I am getting both options here - where am I going wrong here? Or this approach incorrect?
_________________

+1 Kudos if you liked my post! Thank you!

Kudos [?]: 15 [0], given: 251

Current Student
Joined: 20 Mar 2014
Posts: 2676

Kudos [?]: 1767 [2], given: 794

Concentration: Finance, Strategy
Schools: Kellogg '18 (M)
GMAT 1: 750 Q49 V44
GPA: 3.7
WE: Engineering (Aerospace and Defense)
If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

24 Oct 2015, 07:55
2
KUDOS
sagar2911 wrote:

Hi Karishma,

I tried another approach, but got stuck - can you hep me solve by this method?
x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E
x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y
Now x + y = 7 - |6 + 2y|
If we take y = -1, we get x + y = 3 = Option A
If we take y = -2, we get x + y = 5 = Option C
I am getting both options here - where am I going wrong here? Or this approach incorrect?

You are making a mistake with using |6+2y|

After you get x=6+2y and substitute in equation (1), you get 6+2y+|6+2y|+y=7 ---->6+3y+|6+2y| = 7 ---> 3y+|6+2y| = 1. Now the point to note is that the 'nature' of |6+2y| changes at y=-3 and thus you need to evaluate |6+2y| for values smaller than -3 and for values greater than -3.

You have already assumed that y<0 in order to get x=6+2y, so your ranges to consider become -3 $$\le$$q y < 0 and y < -3

Case 1: -3 $$\le$$ y < 0, giving you |6+2y| $$\geq$$ 0 ----> 3y+|6+2y| = 1 ---> 3y+6+2y = 1 ---> 5y=-5 ---> y=-1. Acceptable value giving you x=6+2y = 4 --> x+y = 3

Case 2: y<-3 ---> |6+2y| = -(6+2y) ---> 3y+|6+2y| = 1 ---> 3y-6-2y = 1 ---> y=7 this contradicts the assumption that y<-3 , making this out of scope.

Thus the only value of x+y = 3.

Kudos [?]: 1767 [2], given: 794

Manager
Joined: 08 Sep 2012
Posts: 66

Kudos [?]: 15 [0], given: 251

Location: India
Concentration: Social Entrepreneurship, General Management
WE: Engineering (Investment Banking)
Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

24 Oct 2015, 09:52
Engr2012 wrote:
sagar2911 wrote:

Hi Karishma,

I tried another approach, but got stuck - can you hep me solve by this method?
x + |x| + y = 7 => x + y = 7 - |x| => Whatever be the value of x, |x| will be always non-negative => x + y has to be less than 7 => This eliminates option E
x + |y| - y = 6 => Now, if y is positive, then this equation becomes x = 6 => on substituting in above eqn, we get y = -5 => x+y = 1 => Not present in any of the options => y is negative => x - y - y = 6 => x - 2y = 6 => x = 6 + 2y
Now x + y = 7 - |6 + 2y|
If we take y = -1, we get x + y = 3 = Option A
If we take y = -2, we get x + y = 5 = Option C
I am getting both options here - where am I going wrong here? Or this approach incorrect?

You are making a mistake with using |6+2y|

After you get x=6+2y and substitute in equation (1), you get 6+2y+|6+2y|+y=7 ---->6+3y+|6+2y| = 7 ---> 3y+|6+2y| = 1. Now the point to note is that the 'nature' of |6+2y| changes at y=-3 and thus you need to evaluate |6+2y| for values smaller than -3 and for values greater than -3.

You have already assumed that y<0 in order to get x=6+2y, so your ranges to consider become -3 $$\le$$q y < 0 and y < -3

Case 1: -3 $$\le$$ y < 0, giving you |6+2y| $$\geq$$ 0 ----> 3y+|6+2y| = 1 ---> 3y+6+2y = 1 ---> 5y=-5 ---> y=-1. Acceptable value giving you x=6+2y = 4 --> x+y = 3

Case 2: y<-3 ---> |6+2y| = -(6+2y) ---> 3y+|6+2y| = 1 ---> 3y-6-2y = 1 ---> y=7 this contradicts the assumption that y<-3 , making this out of scope.

Thus the only value of x+y = 3.

Excellent. Thank you dude!
_________________

+1 Kudos if you liked my post! Thank you!

Kudos [?]: 15 [0], given: 251

Non-Human User
Joined: 09 Sep 2013
Posts: 15708

Kudos [?]: 281 [0], given: 0

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

01 Jan 2017, 12:21
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________

Kudos [?]: 281 [0], given: 0

Intern
Joined: 12 May 2017
Posts: 14

Kudos [?]: 0 [0], given: 0

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y = [#permalink]

### Show Tags

12 Jun 2017, 13:55

I understand that if you first that x= pos. and y= neg. you get x=6 and y=-5.

But then this wouldn't be right, because it would contradict the assumptions that x should be neg. and y should be pos.

I don't understand, where do i get these assumptions from?

Kudos [?]: 0 [0], given: 0

Re: If x + |x| + y = 7 and x + |y| - y =6 , then x + y =   [#permalink] 12 Jun 2017, 13:55
Display posts from previous: Sort by